Draft Annual Plan 1993-94 Part I-Plan in Outline - Analysis of Sectoral Outlays and Statistical Statements Government of Goa - Planning Commission (Planning Commission, 1992)
Goa became a full-fledged State in May,1987. Prior to that it was an U.T. alongwith Daman and Diu since liberation in 1961. Goa , has an area of 3702 sq.kms. with a population of 11.69 lakhs as per 1991 Census and a density of 316 persons per sq.km. The State comprises of two districts, namely-North Goa with six talukas and South Goa with five talukas. The State is organised in 398 villages of which 389 are inhabited The villages are grouped into 183 Village Panchayats. Besides, there are 13 towns all of which are Municipalities.
Directorate of Planning, Statistics and Evaluation, Government of Goa